Lessons From a Preservice Teacher: Examining Missed Opportunities For Multicultural Education in an English Education Program - Amy M Vetter; Jeanie Reynolds (Networks: An Online Journal for Teacher Research, 2012)
I had to get to know them [his students]. Because I am disconnected from Black culture a lot, honestly. You get people who assume I’m Black or I’m not. Before I even started teaching the very first question that I got asked was what color are you? And I never knew how big of deal that would be. This was one of many experiences that James described in an interview after being asked how his multiracial identities shaped his student teaching experiences. James was one of six preservice teachers that we followed in our program for three semesters in an attempt to learn more about how to better educate future high school English teachers. As his former instructors in undergraduate English Education courses, we viewed our job as providing support, facilitating dialogue, and sharing expertise with James and other teacher candidates to help them deal with the challenges of student teaching, including those related to race, class, gender and sexuality. It was not until this interview after he graduated, however, that we learned about how James’s multiracial identities shaped his student teaching experiences. We realized that as White, middleclass female instructors and researchers, we lacked insight into what it was like for James to be both an insider and outsider within the context of a public high school. In fact, we made assumptions about James and his needs rather than asking him to reflect on how his race and ethnicities shaped his experiences. As a result, James’s described experiences challenged us to transform our teaching practices and curriculum to engage all students in critical examinations about how race and culture shapes teaching and learning (Banks et al., 2005; Cochran-Smith, 1995).